In host evolution of beta lactam resistance during active treatment for Pseudomonas aeruginosa bacteremia - Spottiswoode, Natasha; Hao, Samantha; Sanchez-Guerrero, Estella; Detweiler, Angela M.; Mekonen, Honey; Neff, Norma; Macmillan, Henriette; Schwartz, Brian S.; Engel, Joanne; DeRisi, Joseph L.; Miller, Steven A.; Langelier, Charles R. (Frontiers in Cellular and Infection Microbiology, 2023)
Multidrug-resistant (MDR) Pseudomonas aeruginosa has been declared a serious threat by the United States Centers for Disease Control and Prevention. Here, we used whole genome sequencing (WGS) to investigate recurrent P. aeruginosa bloodstream infections in a severely immunocompromised patient. The infections demonstrated unusual, progressive increases in resistance to beta lactam antibiotics in the setting of active treatment with appropriate, guideline-directed agents. WGS followed by comparative genomic analysis of isolates collected over 44 days demonstrated in host evolution of a single P. aeruginosa isolate characterized by stepwise acquisition of two de-novo genetic resistance mechanisms over the course of treatment. We found a novel deletion affecting the ampC repressor ampD and neighboring gene ampE, which associated with initial cefepime treatment failure. This was followed by acquisition of a porin nonsense mutation, OprD, associated with resistance to carbapenems. This study highlights the potential for in-host evolution of P. aeruginosa during bloodstream infections in severely immunocompromised patients despite appropriate antimicrobial therapy. In addition, it demonstrates the utility of WGS for understanding unusual resistance patterns in the clinical context.